Adesão ao tratamento medicamentoso em insuficiência cardíaca - Freitas, Elis Marra da Madeira (2018)
Pharmacological treatment for heart failure evolved in the last decades. Betablockers, angiotensin converting enzyme inhibitors, angiotensin II receptor blockers and aldosterone antagonists have been widely used, as they were proven to reduce morbi/mortality in heart failure. Patient adherence has been studied all over the world in the last years in acute and chronic heart failure. Many factors knownly can influence the patient adherence to treatment. This study purpose was to evaluate pharmacological treatment in patients diagnosed with heart failure in outpatient follow up in a university hospital. Different methods were used to get to this objective, comparing each other and also clustering patients in more adherent and less adherent to pharmacological treatment, furthermore, we described the factors influencing patient adherence to pharmacological treatment. Thereunto, the Morisky questionnaire was used. Also a questionnaire made by the author and a form to collect data in patient’s chart were applied. Data frequency was described and then hierarchic clusters analysis was performed. Adherence measured by the Morisky questionnaire resulted in 71% of patients more adherent to pharmacological treatment and 26% less adherent. A different result and with more expressive values was found in the self-report adherence to pharmacological treatment by the patient, where 90% of the patients considered themselves as more adherent to pharmacological treatment and 8% considered themselves as less adherent. When comparing treatment prescribed and treatment reported by the patients, the majority of patients (78%) reports at least one drug different from the prescription. When measured by different methods, adherence can show not uniform results. The clinical factors and factors related to the satisfaction with the service did not influence the patient adherence to pharmacological treatment. In the other hand, some sociodemographics factors, like age (p = 0,0476), employment condition (p = 0,0132), schooling (p = 0,0167), marriage status (p = 0,011), family income (p = 0,0123), and factors related to the use of medications, as having family help to the the medications (p = 0,006), use medication alone (p = 0,0186) and have medical orientation bout the use of medication (p = 0,0077) had influence in patient adherence to pharmacological treatment. Thus, it was observed that patients being followed up in the Heart Failure Clinic of Hospital das Clínicas da Universidade Federal de Goiás are well medicated and have satisfactory adherence to pharmacological treatment.